A inserção das mulheres no magistério capixaba : desdobramento possíveis no trabalho docente no Estado do Espírito Santo (1845-1920) - Alvarenga, Elda (2018)
Investigates the historical process of insertion of women in the public primary teaching and its consequences for the teaching work in the State of Espírito Santo (1845-1920). Focuses on elements that permeated the transition from a profession initially exclusively performed by men, to a feminized professional activity, using as axes of analysis the expansion of access to schooling and the performance of the “Normal School” in the process of female occupation of the public teaching profession and its later feminization. The thesis argues that women's entry into teaching is inextricably linked to the expansion of basic education for both sexes, since, in order to meet the social standards of the studied period, women were called to teach girls, at the same time that, due to the general lack of normalistas, their presence was also necessary in mixed classroms.This research is based on the following hypotheses: the expansion of girls' access to schooling opened the door to the increasing presence of women in teaching, boosting female participation in the “Normal Course” the main training and habilitation tool for teachers in the interstitial. The research had as reference the beginning of the work of the teachers in the public schools of Espírito Santo in 1845, and its generalization, or feminization in 1920. It is oriented in the historiographic practice of index base, having as main reference the studies by Carlo Ginzburg (1989, 1990, 1991, 2002, 2006, 2007, 2013). It is located in the field of History of Education, more specifically in the History of Education in the State of Espírito Santo. The documentary corpus consists of: legislative regulations of the period in question; ordinances and resolutions of the Secretariat of Instruction concerning teachers; administrative investigations of inspectors and school directors and certificates of the “Normal School”; tuition and teaching books; reports and messages from presidents; vice presidents and governors of Espírito Santo; articles published in the local periodical press (news, official and pedagogical); inspection reports; bibliographic and imagery sources. It is considered that the beginning of the work of women in primary teaching in Espírito Santo occurred in 1845, with the hiring of the teacher Maria Carolina Ibrence who occupied the first female teaching chair of the province's capital. From the entry of the first teacher to the end of the century, the growth in the number of girls' enrollments was negligible, while the mixed classes and schools contributed significantly to the increase in the participation of women as teachers. In the meantime, the reforms of education undertaken by Moniz Freire (1892) and Gomes Cardim (1908) promoted changes in primary education in Espírito Santo by improving the institutionalization of public education, expanding enrollments in public schools for both sexes, reformulating the “Normal School” and establish parameters for the professionalization of the teaching profession, with the “Normal School”as a privileged locus for the training of female teachers. In 1920, it is already possible to observe the majority presence of women both in teaching in primary schools of the State and in the “Normal School”. It is concluded, therefore, that the process of feminization of teaching began to be drawn in the last two decades of the nineteenth century and was consolidated in the second decade of the twentieth century. They established this process: the creation and proliferation of mixed schools, the expansion of compulsory primary education for females, the consolidation of the “Normal School” and the removal of men from primary teaching. These elements, as a whole, drove the feminization of the Capixaba teaching in the period under investigation.